Tiktok Algorithm and Its Impact on Marketing Strategy - Setyawan, Aries (RADINKA JAYA UTAMA PUBLISHER, 2024)
Online marketing uses many media, including TikTok, which businesses use. According to the study, people widely use TikTok, a new social networking site in Indonesia, to build businesses and jobs. This study aimed to identify and explain the difficulties associated with implementing learning assessments in the era of self-directed learning. This study uses a descriptive qualitative approach, which is a type of research that relies on data to explain existing theories and develop new theories. TikTok's algorithm enables marketers to target specific demographics with their ads. To get the best digital marketing results from TikTok, you must understand how the algorithm works, monitor trends, and properly engage with the community. TikTok is a platform that prioritizes innovation and short videos created by marketers who always follow trends, actively interact with their audience, and follow trends. Digital marketing necessitates a thorough understanding of the TikTok algorithm, as it enhances active engagement and empowers users. Through algorithm knowledge, sellers can improve marketing content results. TikTok needs to interact with its audience creatively, effectively, and relevantly to achieve its marketing goals.